Pengenalan Media Pembelajaran Digital berbasis Aplikasi Android untuk Anak Prasekolah pada Pendidik Lembaga PAUD - Fitri Alfarisa; Lizza Suzanti; Rr Deni Widjayatri; Rika Ar Nurazka; Firda Rahmadini; Desi Safitri; Alifah Audina (Jurnal Pengabdian Masyarakat PGSD, 2022)
In the current era, a kindergarten teacher or educator must be smarter in sorting the available digital content based on children's developmental achievements but still freely and easily accessible. Mobile application is one preferable media that can be utilized. This community service aimed to (1) introduce and provide training on the use of android application-based digital learning media for preschoolers to kindergarten educators in Serang City, Banten, and (2) examine the level of satisfaction of kindergarten educators regarding content presented in the Giat Bergerak and EduGame MARU applications. This community service used online training methods through the Zoom application, targeting 45 early childhood educators. Stages of activities include preparation, implementation, and evaluation of the results of activities. The Giat Bergerak mobile application consists of content for gross and fine motor activities, educational games, and information on children's health and safety; while the EduGame MARU application contains content introducing and playing simple concepts of numbers, algebra, geometry, statistics, and probability. Furthermore, on average above 90% of early childhood educators who participated in the program expressed their satisfaction with the Giat Bergerak and EduGame MARU applications which were seen from four aspects, namely content quality, alignment of learning objectives, feedback, and motivation.